Implementasi CEDAW (Convention on the Elimination of All Forms of Discrimination against Women) di India: Studi Kasus Diskriminasi Perempuan dalam Tradisi Pemberian Dowry/Mahar - Wiwik Sukarni Pertiwi; Alfian Hidayat; Khairur Rizki (The Department of International Relations Universitas Mataram, 2021)
This study aims to analyze the implementation of CEDAW (Convention on the Elimination of All Forms of Discrimination against Women) against discrimination of women in the dowry tradition of India. This study uses the concept of feminism to find out the problem of female discrimination arising from the dowry culture in India, the concept of good governance to understand how the role of the government in handling the dowry issue and the concept of International organization to understand the roles of organizations involved in helping India handle the issues of discrimination stemmed from the dowry culture. This research is a qualitative descriptive research, which uses secondary data derived from library research as its data collection technique. The data is analyzed through five steps: reading, studying significances, data classification, finding patterns and framework construction. The results shows that violence in terms of the tradition of giving dowry is included in cultural violence, because dowry arises from the Hindu tradition which requires the bride to pay dowry to the groom before marriage. In resolving the problem of discrimination against women in the country, the Indian government is not only alone, the Indian government is also assisted by international organizations such as UN Women and CARE.